Re-examination of Borradaile's Urocaris longicaudata specimens from the 1905 J.S. Gardiner Collection (Crustacea: Decapoda: Pontoniinae) - Bruce, A. J. (Zootaxa, 2007)
Borradaile’s five specimens referred to Urocaris longicaudata from the Seychelle and Maldive Islands have been re-examined. Although incomplete and not in good condition, they can be distinguished from all of the twelve described species of the Periclimenes aesopius species group to which they belong and they are now briefly described as new. The Seychelle specimens were collected from 70m, unusually deep for species of this group.